Student Model and Elimination of Examination Malpractices - The Zambian Case - Katete, Rodrick Symon; Kalonga, Given (The Journal of Educational Development, 2019)
The problem of examination malpractices has persisted in many primary and secondary schools in Zambia for a decade now. Records show that there has been an annual recurrence of examination malpractices for the period 2008 to 2018. In 2018, the initial examination papers for Grades 9 and 12 had to be canceled and new ones set after the examination papers were leaked on social media. These malpractices reported in the last decade have the potential to negatively affect the quality of graduates from the concerned schools. It may further cast doubt on the validity and reliability of the certificates conferred. To a wider extent, examination malpractices have the potential to lead to cultural decay, increased criminality, social injustices and corruption in society. The driving factors to malpractices have been identified as macro and micro in nature. The study introduces a new model coined the 13-selfs model. Using the introduced model, the study proposes solutions to the internal factors. With this new model it is possible to nurture a student with higher confidence and integrity leading to the elimination of malpractices. The thirteen elements of the 13-Selfs model are self-confidence, self-esteem, self-motivation, self-determination, self-organization, self-equipped, self-sustenance, self-conviction, self-efficacy, self-assurance, self-sufficiency, self-control, self-defense. The proposed solutions to the macro factors include the use of modern technology such as drones to secure and deliver examination materials on the day of examination. The use of micro-chipped examination papers has also been proposed to monitor in real time the location and conditions of materials.